A BRIEF REVIEW ON INNOVATIVE ANATOMY LEARNING TECHNOLOGIES FOR MEDICAL AND HEALTH STUDENTS’ EDUCATION - Fernandes de Oliveira, Vanessa; Ramos, Amanda Pereira; Tomaz , João Felipe Martins; Reis, Marcello Carvalho dos; Pereira, Eduardo da Silva; Gondim , Victor José Timbó; Santana, Rafael Dantas; Alexandria, Auzuir Ripardo; Albuquerque , Victor Hugo Costa (RECISATEC - REVISTA CIENTÍFICA SAÚDE E TECNOLOGIA - ISSN 2763-8405, 2022)
Contribution: Considering the rapidity of the emergence of new technologies in the modern world, it is necessary to identify and describe potential educational innovations and technologies used as tools for improving healthcare students anatomy learning in the last years. The key contribution of this study is to indicate implementation and other challenges to be overcome. Background: Extensive research demonstrated that several different innovative methods have been used for anatomy teaching. Based on these findings, discussing the most recent existing technologies may be worthwhile. Research Questions: What innovative technologies are being used as tools for improving healthcare students Anatomy learning? What are the main challenges and perspectives related to them? Methodology: This review discussed studies published from 2019 to 2021 found in Embase, IEEE Digital Library, Pubmed, ScienceDirect and Web of Science. Inclusion and exclusion criteria were established and a quality assessment was conducted aiming to mitigate biases and systematic errors. Findings: The databases electronic search identified 149 references and only 10 studies met the minimum cutoff score and were discussed. Compared to traditional methods, alternative learning technologies are excellent ways to improve and transform the education in the health’ system, making it more efficient, economic, practical and accessible.